Carbonic anhydrase II deficiency syndrome in a Belgian family is caused by a point mutation at an invariant histidine residue (107 His----Tyr): complete structure of the normal human CA II gene. - Venta, P J (1991)
Carbonic anhydrase II (CA II), which has the highest turnover number and widest tissue distribution of any of the seven CA isozymes known in humans, is absent from the red blood cells and probably from other tissues of patients with CA II deficiency syndrome. We have sequenced the CA II gene in a patient from a consanguinous marriage in a Belgian family and identified the mutation that is probably the cause of the CA II deficiency in that family. The change is a C-to-T transition which results in the substitution of Tyr (TAT) for His (CAT) at position 107. This histidine is invariant in all amniotic CA isozymes sequenced to date, as well as the CAs from elasmobranch and algal sources and in a viral CA-related protein. His-107 appears to have a stabilizing function in the structure of all CA molecules, and its substitution by Tyr apparently disrupts the critical hydrogen bonding of His-107 to two other similarly invariant residues, Glu-117 and Tyr-194, resulting in an unstable CA II molecule. We have also completed the intron-exon structure of the normal human CA II gene, which has allowed us to prepare PCR primers for all exons. These primers will facilitate the determination of the mutations in other inherited CA II deficiencies.